Subconjunctival dexamethasone-assisted conjunctival autograft harvesting versus normal saline during pterygium surgery – A randomized clinical trial - Ashok Meena; Ashish Agrawal; Gautam Parmar; Bharat Gurnani (Indian Journal of Ophthalmology, 2024)
Purpose: To evaluate the effect of subconjunctival dexamethasone compared to normal saline on conjunctival autograft harvesting in patients undergoing pterygium surgery. Methods: Fifty-two eyes of 52 patients who underwent pterygium excision combined with autologous conjunctival graft (CAG) using releasable suture were included in this prospective interventional study. The patients were randomized into two groups of 26 patients each. Group A consisted of patients in whom CAG was harvested using subconjunctival 0.5 ml of 0.4% dexamethasone sodium phosphate and in group B patients, normal saline was used. The patients were assessed for postoperative pain, foreign body sensation, and watering as the subjective signs of inflammation and conjunctival inflammation and lid edema as the objective signs of inflammation at 12 and 24 h postsurgery. Results: The mean age of group A and B patients was 47.69 + 13.09 and 46.00 + 10.76 years, respectively. The male:female ratio was 1.6:1 in group A and 1.1:1 in group B. The mean surgical time in group A was 243.96 ± 52.13 s and in group B was 258.08 ± 43.99 s. Postoperative pain, foreign body sensation, and watering were significantly lower in group A patients than in group B patients at both 12 and 24 h postoperatively (group A: 4.65 ± 1.33, 4.88 ± 1.73, and 3.85 ± 1.43, respectively, at 12 h; 1.89 ± 1.03, 1.69 ± 1.09, and 1.69 ± 0.97, respectively, at 24 h and group B: 6.42 ± 0.95, 6.65 ± 0.98, and 6.27 ± 1.40, respectively, at 12 h; 3.27 ± 1.43, 3.12 ± 1.25, 2.58 ± 1.14, respectively, at 24 h) (P < 0.001). Conjunctival inflammation was significantly lower in group A at 12 h (P < 0.05) and 24 h (P < 0.05) after surgery compared to group B. Lid edema failed to show any significant (P = 0.17) difference with respect to severity in both the groups at 12 and 24 h (P = 0.699). Conclusion: Subconjunctival dexamethasone decreased patient discomfort following pterygium surgery. The dexamethasone group had reduced conjunctival inflammatory signs without any notable complications.